ANALISIS HUKUM PIDANA DAN KRIMINOLOGI TERHADAP TINDAK PIDANA PENISTAAN AGAMA DI INDONESIA - Nurul Safrina; Yusrizal Yusrizal; Zulkifli Zulkifli (Jurnal Ilmu Hukum Reusam, 2022)
Blasphemy is one of the criminal acts of insulting and degrading a religion. Blasphemy comes from two words, namely blasphemy and religion, blasphemy comes from the word blasphemy which means low blasphemy. Religion also means a deliberate attack on the good name and honor of another person or a groups both orally and in writing with the aim of being known by the wider community.The purpose of the research from the perspective of criminal law is to look at the concept of accountability for criminal acts of blasphemy in Indonesia and the protection of religious law for someone who commits blasphemy, while from a criminological perspective to look at the arrangements for criminal liability for perpetrators of criminal acts of blasphemy in Indonesia and regulations Religion from the Criminal Code (KUHP). The method used in this research is Normative (Normative Legal Research). This type of research uses qualitative research. The research approach that is carried out is more aimed at the statute approach. Conceptual Approach The nature of the research in this thesis is descriptive research. The form of this research is a form of prescriptive book of criminal law. The results of this study indicate that the legal arrangement regarding the crime of blasphemy in Indonesia is regulated in Article 156 of the Criminal Code as for the contents of the article which reads: whoever publicly expresses and expresses feelings of hostility, hatred or humiliation towards one or several groups or groups of Indonesian people, threatened with a maximum imprisonment of five years or a maximum fine of four thousand five hundred rupiah. The word group or group in this article is interpreted as part of the Indonesian people who have differences both in terms of religion, place and country, race, descent, nationality or position according to article 156 of the Criminal Code. It is recommended that legal arrangements regarding criminal acts of blasphemy in Indonesia need to be perfected by adding articles that are able to answer all the needs of the community, both in the Criminal Code and the Law of the Republic of Indonesia.